Knowledge, Attitude and Practice of Disposal of Unused, Unwanted and Expired Medicines among Healthcare Professionals - Sarraf, D. P.; Rauniar, G. P.; Kushwaha, R. P.; Keshwar, S.; Maharjan, R. (Kathmandu University Medical Journal, 2022)
Background Unused, unwanted and expired medicines stored at home pose threats to both health systems and environments. Healthcare professionals (HCPs) should be aware of the proper disposal methods of such medicines.Objective To assess the knowledge, attitude and practice of disposal of unused, unwanted and expired medicines among healthcare professionals.Method A web-based cross-sectional descriptive study was conducted among faculties and junior residents at B.P. Koirala Institute of Health Sciences, Dharan, Nepal using a semi-structured proforma. The data were collected through Google Form. Descriptive statistics were calculated. Chi-square test and Student’s t test were used for analysis using statistical package for the social sciences at p value of 0.05.Result A total of 294 healthcare professionals with mean age 35.37± 6.630 years were participated out of which 231 (78.6%) were male and 151 (51.4%) were faculties. Mean knowledge score was higher in faculties (2.37±1.111) than the Junior residents (2.33±1.155) [F(1,293)=0.102, p=0.750]. Junior residents (140 out of 143, 97.9%) had a better attitude than faculties (141 out of 151, 93.3%) regarding the disposal of medicines [χ2 (1)=3.558, p=0.059]. Junior residents (36 out of 143, 25.1%) also had a better practice than faculties (24 out of 151, 15.8%) regarding the disposal of medicines [χ2 (1)=3.895, p=0.048].Conclusion Majority of the Healthcare professionals had positive attitude but poor knowledge and practice regarding disposal of expired and unused medicines. There was a high practice of keeping medicines at home by healthcare professionals. The findings would be useful for planning strategies to minimize unused medicines and foster the appropriate disposal practice.